PERBANDINGAN PEMBAGIAN HARTA WARIS DALAMPERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT - Iswawan Sulaiman; Ibnu Jazari; Khoirul Asfiyak (Jurnal Hikmatina, 2019)
Islamic inheritance law is a rule that regulates the transfer of property from a deceased person to another person to give property to an heir who is part of obtaining inheritance according to the portions that have already become a portion that will divide to the heirs given by the heir. "In our country, the Republic of Indonesia, the applicable national inheritance law has not been formed until now there are three types of inheritance law that are valid and accepted by Indonesian society, namely Islamic law, customary law and European civil law (BW)." (Jazari, 2019: 31) . The form of the inheritance legal system is very related to the system of people who still have family characteristics. In the family system there are still links with Indonesian people who are still based on lineage, which are related to lineage systems such as: Patrilineal, matrilineal and bilateral. However, customary inheritance law in Indonesia is still affected by the lineage system that is still valid in the regions of the community which still uses offspring systems in the form of pure patrilineal systems, alternerend matrilineal or bilateral (although difficult in Indonesia), and also there is a multiple unilateral system (dubbel-unilateral). This lineage system is influenced by the determination of heirs as well as inherited parts of the inheritance (both material and immaterial). The inheritance law in customary law is something that has a connection with the rules about the transfer of property from the deceased to those who are still alive in the distribution of family and relatives. But it has a difference in doing division. Kata Kunci: PerbandinganHarta Waris, Hukum Islam, Hukum Adat